Evaluation and Policy Analysis: A Communicative Framework - Wallat, Cynthia; Piazza, Carolyn (Education Policy Analysis Archives, 1997)
A major challenge for the next generation of students of human development is to help shape the paradigms by which we analyze and evaluate public policies for children and families. Advocates of building research and policy connections point to health care and stress experiences across home, school, and community as critical policy issues that expand the scope of contexts and outcomes studied. At a minimum, development researchers and practitioners will need to be well versed in available methods of inquiry; they will need to be "methodologically multilingual" when conducting evaluation and policy analysis, producing reports, and reporting their interpretations to consumer and policy audiences. This article suggests how traditional approaches to policy inquiry can be reconsidered in light of these research inquiry and communicative skills needed by all policy researchers. A fifteen year review of both policy and discourse processes research is presented to suggest ways to conduct policy studies within a communicative framework.